Tanggung Jawab Hukum Terhadap Pelaksanaan Penempatan Tenaga Kerja Indonesia Ke Luar Negeri - Utama, Jenry Aditstya Ferdana; , Nuswardhani, S.H, S.U; , Darsono, S.H., M.Hum (2015)
Indoensian Workers are Indonesian citizen who works abroad in the determined period to make a living for their family in Indonesia for a better life. Indonesia is included to the highest rate country whose workers are working abroad so instead of decreasing unemployment in Indonesia, it also the biggest source of foreign exchange for Indonesia. For the sake of creating safety in sending the Indonesian workers overseas there is PPTKIS ( Executive placement of private workers) who collaborate along the government to facilitate the people who wants to be Indonesian Workers. Andromeda Graha Surakarta company provides Indonesian Workers sending service for Indonesian Workers such as Brunei Darusallam, Malaysia, and Taiwan by collaborating along govermentm and partners abroad so safety assurance, Indonesian Workers protection and company responsibility can be raelized. So, every form of Indonesian Workers placement, Indonesian Workers protection, and PPTKIS (executive placement of private workers) responsibilities are based on Act No. 39 of 2004 on Placement and Protection of Indonesian Workers Abroad